Target-like chondrocytes with thick perichondrocytic rings in cartilage-forming tumours. Preliminary report - Povýšil, Ctibor; Kaňa, Martin (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2021)
BACKGROUND: Here we present our experience with the occurrence of neoplastic chondrocytes with target-like appearance surrounded with unusual hypertrophic thick eosinophilic perichondrocytic rings (baskets), sometimes containing two or several layers. METHODS AND RESULTS: Pericellular rings (baskets) were positive in APAS and Masson's staining method and showed immunoreactivity with antibody against type IV collagen. Such single cells or small groups of such cells were observed rarely in 3 osteochondromas, 2 skeletal chondromas, 2 extraskeletal chondromas and 2 skeletal and 1 laryngeal chondrosarcomas. Moreover, 1 unusual soft tissue chondrosarcoma was composed entirely of target-like chondrocytes with hypertrophic extremely thick perichondrocytic rings. Such cartilage-forming tumour with target-like cells, which, to the best of our knowledge, is the first such chondrosarcoma reported in the literature. Ultrastructural evidence is presented that perichondrocytic rings have complicated structure.They contained microfibrillar component with abundant admixture of irregular aggregates of dense amorphous non-fibrillar material localised in lacunar spaces. In outer part of the rings predominated microfibrillar structures corresponding to type VI collagen that produced a rather dense capsule-like demarcation line against surrounding intercellular spaces. CONCLUSIONS: The described unusual changes are probably the result of hyperproduction and remodelation of perichondrocytic matrix by abnormal neoplastic chondrocytes in response to unknown factors. Local vascular and molecular signals, may be supposed as probable causes of this phenomenon.
Keywords: chrupavka; chondrocyty; Chondrosarcoma; lidé; Cartilage; Bone Neoplasms; Chondrocytes; nádory kostí; Chondroma; chondrosarkom; chondrom; Humans